Pengembangan Media Pembelajaran Pop Up Book Ilmu Pengetahuan Alam Sekolah Dasar - Imam, Khairul; Kurniawan, Aan Wahyu (Nur Science Institute, 2023)
Background: This study aims to evaluate the validity of the Pop-Up Book media in science education at elementary schools. The purpose of this research is to assess the suitability of the developed pop-up book media for use in the 4th grade of SDN Pajang 3, Surakarta City. Method: The research method employed is Research and Development (R&D), utilizing the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Result: Students are still interested in seeing the Pop-Up Book media from each interesting page and listening to the stories told by the teacher. This makes it easier for students to understand the learning material. Implication: The researcher's aim in developing this media is to attract students' attention during the learning process, prevent student boredom, and create interaction between teachers and students so that learning objectives can be achieved well. Novelty: The present study revealed the implementation of saint assessment in elementary school comprehensively.